Electronic transition dipole moments and dipole oscillator strengths within fock-space multi-reference coupled cluster framework: an efficient and novel approach - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
Within the Fock-space multi-reference coupled cluster framework, we have evaluated the electronic transition dipole moments, which determine absorption intensities. These depend on matrix elements between two different wave functions (e. g., ground state to the excited state). We present two different ways, to calculate these transition moments. In the first method, we construct the ground and excited state wave functions with the normal exponential ansatz of Fock-space coupled cluster method and then calculate the relevant off-diagonal matrix elements. In the second approach, we linearize the exponential form of the wave operator which will generate the left vector, by use of Lagrangian formulation. The right vector is obtained from the exponential ansatz. In order to relate the transition moments to oscillator strengths, excitation energies need to be evaluated. The excitation energies are obtained from the Fock-space multi-reference framework. The transition dipole moments of the ground to a few excited states, together with the oscillator strengths of a few molecules, are presented. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793277]